On-line Tourism Services in Developing Countries: Need for the Website Marketing Infrastructure - Arabi, U. (Indian Journal of Marketing, 2007)
In developing economies the tourism sector is of strategic importance. Currently online tourism is a dynamic growing industry with highly competitive newcomers and powerful concentration mechanisms. Globally the number of online tourism providers has increased over the years and the market has experienced a gradual consolidation in the hands of the larger and better-funded companies. In developing countries the opportunity offered by ICTs is a priority for tourism providers at national, regional and community levels. However, before the Internet, information on tourism opportunities in these countries were mainly generated and maintained by overseas service providers. Now the Internet has underlined the continuous evolution of the tourism industry which drives substantial changes in the market structure and consumer behavior.